The Authority Guide to Conflict Resolution : a Revolutionary Approach to Effective Collaboration. - Gunn, Jane (Authority guides., 2017)
Capture and harness the positive energy in your team and conquer the problems that can harm teamwork, productivity and engagement in your business. Mediation expert Jane Gunn will teach you all the essential skills you need to constructively manage relationship challenges and crisis.